2017
DOI: 10.1016/j.ijscr.2017.07.052
|View full text |Cite
|
Sign up to set email alerts
|

A long-term recurrence-free survival of a patient with the mixed adeno-neuroendocrine bile duct carcinoma: A case report and review of the literature

Abstract: HighlightsMixed adeno-neuroendocrine carcinoma arising primarily in the bile duct is very rare neoplasm.The patient with mixed adeno-neuroendocrine carcinoma in the bile duct indicates a poor prognosis.On imaging studies, a hypervascular tumor is suspicious of mixed adeno-neuroendocrine carcinoma.Curative resection is the only way to obtain the long-term prognosis, even if these patients have lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Interestingly, in 43 studies (n = 61) where more than one diagnostic sample was available [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]30,[32][33][34][36][37][38][39][41][42][43][44][45][46][47]49,50,53,55,[59][60][61][62]64,65,96], the initial diagnosis from the first sample collected (either cytological or histological) was in keeping with MiNEN or suspicion of MiNEN in 36.1% (n = 22) of cases, adenocarcinoma in 36.1% (n = 22), poorly differentiated neuroendocrine carcinoma in 21.3% (n = 13), and well differentiated neuroendocrine tumour in 6.6% (n = 4).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
“…Interestingly, in 43 studies (n = 61) where more than one diagnostic sample was available [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]30,[32][33][34][36][37][38][39][41][42][43][44][45][46][47]49,50,53,55,[59][60][61][62]64,65,96], the initial diagnosis from the first sample collected (either cytological or histological) was in keeping with MiNEN or suspicion of MiNEN in 36.1% (n = 22) of cases, adenocarcinoma in 36.1% (n = 22), poorly differentiated neuroendocrine carcinoma in 21.3% (n = 13), and well differentiated neuroendocrine tumour in 6.6% (n = 4).…”
Section: Clinical-pathological Characteristics Treatment Modalitiesmentioning
confidence: 99%
“…By searching the literature, we found that biliary MANEC is rare, and only one of the retrospective studies mentioned two cases of hepatic MANEC. But it lacked corresponding analysis [10] 0.10 cases of biliary MANEC patients were summarized [10][11][12][13][14][15][16][17][18]. Including 4 cases of distal bile duct, 2 cases of hilar bile duct, 1 case of common bile duct, 1 case of intrahepatic bile duct, 1 case of cystic duct, and 1 case of extrahepatic bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…MANECs predominately occur in the colon, appendix and stomach, where neuroendocrine cells are diffusely distributed (4). MANECs arising from the EHBT are extremely rare, with a total of eight cases reported in the medical literature since the category was introduced in 2010 (1320). The histogenesis of biliary MANEC remains under debate due to the scarcity of enterochromaffin (Kultchisky) cells in the normal bile duct (21).…”
Section: Discussionmentioning
confidence: 99%
“…The search identified 37 patients with NEN in the EHBT since 2010. Eventually, a total of 38 cases, including the present case, were analyzed (Table I) (9,10,1320,2853). Clinical characteristics and survival outcomes among different pathological types were compared, and they are summarized in Table II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation